Work Family Conflict Dan Psychological Well-Being Pada Istri Yang Berkarir Di Toraja Utara - Lembang, Irsah Bunga; Huwae, Arthur (Jurnal Psikologi Udayana, 2022)
Responsibilities in the family are mandatory for each member to fulfill. One of the main responsibilities of a mother is to take care of her husband, children and household chores. However, currently the role of the mother is no longer just taking care of the household, but also making a living to help meet daily needs in order to achieve prosperity in the family. This is also widely done by mothers who are in North Toraja, where many mothers are currently carrying out dual roles as wives and also as career women. The study aims to reveal the relationship between work family conflict and psychological well-being in wives who have a career in North Toraja. The study used quantitative methods with non-probability snowball sampling techniques. The sample number of 52 wives who had a career in North Toraja. The scale used consists of the work family conflict scale and the psychological well-being scale. The results proved that the hypothesis was rejected meaning that there was no significant negative relationship between work family conflict and psychological well-being.